Prevalence of Hepatitis B Virus (Hbv) and Hepatitis C Virus (Hcv) Infections amongst Children in the Wa District Of The Upper West Region Of Ghana. - Avege, A. (University of Ghana, 2016)
Background: Hepatitis B virus (HBV) and Hepatitis C virus (HCV) infections are major global public health problems transmitted primarily through exposure to percutaneous human blood and plasma and other mechanisms known as horizontal transmission. Objectives: The goals of this study were to determine the seroprevalence of HEV and HCV infections, the related risk factors associated with transmission and the knowledge and risk perception of HEV and HCV amongst school children in the Wa district of the Upper West Region of Ghana. Methods: A cross-sectional prevalence study of HBV and HCV infections was conducted amongst school pupils in the study area. Using a multi-stage sampling procedure, a total of 280 children [144 boys (51.4%) and 136 girls (48.6%)] were selected. 5 ml of blood was drawn from each enrolled pupil and the prevalence of hepatitis B surface antigen (HE sAg) and antibodies to hepatitis C virus (anti HCV) assessed using the 3rd generation HEV and HCV ELISA assay kits (Serodia Fujirbro Inc, Japan). Questionnaires were administered to collect information on demography, related risk factors, knowledge and behaviours that might put them at risk of acquiring HEV and HCV infections. Results: The overall seroprevalence for HEsAg was 12.1% [95% (CI) 8%-16%], 10.7% [95% (CI) 7%-14%] for anti-HCV and 2.9% [95% (CI) 1%-5%] for both HEsAg and anti-HCV, with no significant difference between sexes. However, a higher rate of infection was observed in males than in females. HBsAg prevalence differed significantly among the religions: 18.0% and 8.4% among Christians and Moslems respectively. The anti-HCV was also predominantly higher among Christians (15.0%) than in Moslems (7.8%) [p=0.002]. HEsAg and anti-HCV prevalence was highest among the Dargatis than any other ethnic group. Conclusion: This study has demonstrated a high prevalence of HEV and HCV infection among school children in the Wa district. Though prevalence of specific risky behaviours were very high they were not significantly associated with seropositivity. Effective preventive strategies that can help reduce the high prevalence of HBC and HCV infections include ensuring that all newborns access fully their vaccination schedules and the DHMT in collaboration with the Regional Education Directorate of the Ministry of Education, incorporate a comprehensive component on HBV and HCV infections into the schools health syllabus.
Theses (MPh) - University of Ghana, 2016.